The Daddy Double-Bind: How the Family and Medical Leave Act Perpetuates Sex Inequality Across All Class Levels - Palazzari, Kari (Columbia Journal of Gender and Law, 2007)
For over a decade there has been a great deal of discussion in America about work-family conflict or work-life balance. These discussions have typically focused on the plight of women, mothers in particular, and the inhospitable labor market. Advocates who seek to improve the status of women have been vocal in demanding changes in the workplace. In response, employer policies like job sharing and flextime have become common and awards for the most “family-friendly” workplace are readily visible. Despite all of this commotion, however, there is a persistent tension between employer expectations and employee responsibilities. Employers still espouse ideal worker norms that require long hours and uninterrupted tenures, which were established by the breadwinner/homemaker family model of the mid-twentieth century. Meanwhile, most families need two wage-earners just to make ends meet. With the continuing decline in real wages, many families simply cannot afford to have one parent stay home. Sociologist Theda Skocpol notes, “[I]n the late 1950s, a high-school educated father could make enough to sustain a family consisting of a homemaker mother and two children at an economic level above the poverty line.” Today, only thirty-one percent of married couples with children under eighteen have a father who works and a mother who does not. Skocpol observes, “[W]e no longer have an economy centered around the father-breadwinner who goes off to work at a full-time (or more), well- paid, lifetime job, leaving behind a mother to care for the home and family. Instead, single-parent or two-worker families are prevalent.”